Global profiling of viral and cellular non-coding RNAs in Epstein–Barr virus-induced lymphoblastoid cell lines and released exosome cargos. (1st March 2017) - Gallo, Alessia; Vella, Serena; Miele, Monica; Timoneri, Francesca; Di Bella, Mariangela; Bosi, Silvia; Sciveres, Marco; Conaldi, Pier Giulio
Abstract: The human EBV-transformed lymphoblastoid cell line (LCL), obtained by infecting peripheral blood monocular cells with Epstein–Barr Virus, has been extensively used for human genetic, pharmacogenomic, and immunologic studies. Recently, the role of exosomes has also been indicated as crucial in the crosstalk between EBV and the host microenvironment. Because the role that the LCL and LCL exosomal cargo might play in maintaining persistent infection, and since little is known regarding the non-coding RNAs of LCL, the aim of our work was the comprehensive characterization of this class of RNA, cellular and viral miRNAs, and cellular lncRNAs, in LCL compared with PBMC derived from the same donors. In this study, we have demonstrated, for the first time, that all the viral miRNAs expressed by LCL are also packaged in the exosomes, and we found that two miRNAs, ebv-miR-BART3 and ebv-miR-BHRF1-1, are more abundant in the exosomes, suggesting a microvescicular viral microRNA transfer. In addition, lncRNA profiling revealed that LCLs were enriched in lncRNA H19 and H19 antisense, and released these through exosomes, suggesting a leading role in the regulation of the tumor microenvironment. Highlights: LCL are widely used for genetic, pharmacogenomic, immunologic and therapeutic studies. We provide the comprehensive characterization of LCL and their exosomes cargo. Our results emphasize the potential role of ncRNAs in EBV biology and tumorigenesis. The abundance of two EBV-miRNAs in LCL exosomes might suggest a selective transfer.